Hubungan Konsumsi Fast Food dan Aktivitas Fisik dengan Kejadian Gizi Lebih pada Remaja di SMP Pelita Raya Kota Jambi - Hanifa Rahmi Syafira, Regita; Gustra Jeki, Andicha; Fatmawati, Tina Yuli; Wulansari, Arnati (3031-8572, 2024)
Fast food is a type of food that is easy to serve quickly or practically processed. Fast food contains a lot of salt, sugar, calories and fat. The high calorie content of fast food, if not balanced with active activity or exercise, is detrimental to health, as it can trigger future disease and lead to overnutrition. The purpose of this study was to determine the relationship between fast food consumption and physical activity with the incidence of overnutrition in adolescents at Pelita Raya Junior High School, Jambi City. This type of research is quantitative research with cross-sectional design. Data was collected by distributing FFQ questionnaires, GPAQ questionnaires and measuring BMI. This study was conducted in June 2024 in Pelita Raya Junior High School, Jambi City. Data analysis in the study used univariate and bivariate analysis using chi-squared test to determine the relationship between the independent variable (fast food consumption and physical activity) with the dependent variable (overnutrition). The results showed the percentage of adolescents who consumed fast food with frequent categories as many as 15 adolescents (42.9%) and rarely as many as 20 adolescents (57.1%). The picture of physical activity of adolescents with high intensity as many as 21 adolescents (60%) and low as many as 14 adolescents (40%). The nutritional status of adolescents with overnutrition category was 13 adolescents (37.1%) and normal nutritional status was 22 adolescents (62.9%). There is a relationship between fast food consumption and the incidence of overweight (p = 0.015) and there is a relationship between physical activity and the incidence of overweight (p = 0.000). In this study it can be concluded that there is an association between fast food consumption and physical activity with nutrient intake. It is recommended that adolescents reduce their consumption of fast food, adopt good consumption patterns and engage in sufficient physical activity to avoid overnutrition.